A Comparison of Heart Rate Variability Metrics Between Apolipoprotein E ε4 Carriers and Non‐Carriers in Cognitively Normal Middle‐Aged Adults. (20th December 2022) - Anderson, Travis; Slutsky‐Ganesh, Alexis B; Wideman, Laurie; Park, Kyoung Shin; Labban, Jeffrey D; Kibildis, Samuel; Vance, Jarod C; DuBois, Samantha L; Holder, Hadassah; Etnier, Jennifer L
Abstract: Background: The Apolipoprotein E (APOE) ε4 allele has been identified as a critical genetic risk factor for developing Alzheimer's disease. Heart rate variability (HRV) metrics are non‐invasive indicators of autonomic nervous system function associated with cognitive performance in patients with dementia and mild cognitive impairment. Some evidence suggests reduced HRV complexity in elderly adults carrying the ε4 allele beyond the effects of aging. However, no study has evaluated whether cognitively normal middle‐aged adults differ in their HRV based on their APOE carrier status. Method: The present cross‐sectional analysis was based on the larger Physical Activity and Alzheimer's Disease 2 clinical trial (NIH: R01AG058919). Eighty‐six cognitively normal middle‐aged adults (sex: 85.9% female; age: 57.5±5.9 years; height: 166.5±8.8 cm; mass: 78.3±18.8 kg) had height, mass, and resting blood pressure assessed and completed a series of surveys. Participants provided a saliva sample via passive drool to determine APOE ε4 carrier status and also completed a 5‐minute seated electrocardiogram assessment. R‐waves were identified, and the RR interval time series were filtered prior to HRV analysis. HRV metrics of the standard deviation of the normal‐to‐normal interval, root mean square of successive differences, high and low‐frequency power, and sample entropy were calculated. Differences in HRV metrics between ε4 carriers (n = 32) and non‐carriers (n = 54) were tested via general linear models. Differences were also tested after controlling for sex, age, education, ethnicity, body mass index, moderate to vigorous physical activity, and mean arterial pressure. Result: No differences in any HRV metric were observed between APOE ε4 carriers and non‐carriers (all p's > 0.05), including after controlling for all and sets of covariates. Conclusion: The absence of significant associations between carrier status and HRV in cognitively normal adults suggests that HRV is not predictive of Alzheimer's disease risk in the same manner as genetic factors. Rather, HRV may be concurrently altered with cognitive decline and thus serve as a non‐invasive biomarker that could be monitored to indicate when more intensive cognitive testing is required. Future research should test the similarity in HRV and cognition trajectories in APOE ε4 carriers and non‐carriers.